Production of recombinant Chitinase from Trichoderma virens Ukm-1 in E.Coli - Hassan, Nursia (2007)
The main objective of this study is to enhance the production of recombinant chitinase from Trichoderma virens UKM-1 in E.coli in the form of soluble/active protein.